Pharmacognosy; the knowledge about drugs and their natural sources / Dr. Nurhuda Manshoor - Manshoor, Nurhuda (Faculty of Pharmacy, 2023)
The word pharmacognosy consists of two Greek words: pharmakon, which means 'a drug', and gnosis, which means 'knowledge'. In this field of science, researcher deals with the secondary metabolites found in many plants, animals, and microbial natural sources. The history of medication is as recent as human civilization. Herbal medicines, as a major remedy in the ancient system of medicine, have been employed in medical practices since antiquity. The first records of knowledge documentation were produced by Shen Nung (a Chinese emperor) in 2500 BC, describing different recipes of drug preparation from more than 300 medicinal plants for the management of numerous human diseases. Records had it that the use of plants (herbs) as medicine started gaining momentum around 500 BC, though prior to this period, their use was not limited to healing but believed to possess spiritual (ritual) power as well.